An initial approach to the concept of responsible consumption among Mexican university students - Paredes, Ana M.; Muñoz, Luis F. (European Journal of Economics and Business Studies, 2023)
Since the last century, there has been an international concern to modify production processes and consumption habits that have harmful social, economic and environmental effects. In 2015, the 2030 Agenda for Sustainable Development was formulated, from which the Sustainable Development Goals are derived. This has motivated the development of research on the characteristics of responsible consumption and on how to promote its practice at a mass level. Thus, the general objective of this study was to analyze the way in which young university students define socially responsible consumption, as well as the way in which it could be promoted. To this end, an exploratory, qualitative, cross-sectional study was designed, gathering information through in-depth interviews with university students. Among the results, it stands out that the respondents have a general knowledge of the implications of responsible production and consumption, which they associate mainly with care for the environment; they also perceive that the consumer has the power to influence the practices of companies. On the other hand, they consider that consuming responsibly brings benefits, but at the same time, demands additional efforts and expenses. To promote responsible consumption, they propose massive campaigns on social networks aimed at young people. In conclusion, it can be said that the group interviewed, knows the advantages and benefits of responsible consumption, but there are not strong enough and concrete incentives to change habitual consumption behavior.